2005
DOI: 10.1159/000084288
|View full text |Cite
|
Sign up to set email alerts
|

Wrestling Injuries

Abstract: There are several potential areas for decreasing injury risk in wrestlers, including equipment, coaching, officiating and training. However, informed decisions with regard to preventing injuries are dependent upon the quality of the basic epidemiological data available, and at this time, analyses of risk factors and potential preventive measures are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 0 publications
1
41
0
2
Order By: Relevance
“…Targeting football-and wrestling-specific interventions to limit shoulder injuries with a focus on appropriate protective equipment, an emphasis on proper tackling and wrestling technique, and stricter enforcement of rules by referees may result in significantly lower numbers of shoulder injuries in this population. 38,39 More than 3 times as many shoulder injuries in our study were sustained during competition as compared with a Groups without asterisks were used as referent (ie, for strain/sprain, boys were used as the referent group). b Statistically significant (95% CI excludes 1.00).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting football-and wrestling-specific interventions to limit shoulder injuries with a focus on appropriate protective equipment, an emphasis on proper tackling and wrestling technique, and stricter enforcement of rules by referees may result in significantly lower numbers of shoulder injuries in this population. 38,39 More than 3 times as many shoulder injuries in our study were sustained during competition as compared with a Groups without asterisks were used as referent (ie, for strain/sprain, boys were used as the referent group). b Statistically significant (95% CI excludes 1.00).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have indicated the incidence of upper extremity injuries in high school wrestlers was higher 1,9,15 than the incidence of lower extremity injuries in collegiate wrestlers. 1 These contrasting data are similar to those for the BJJ fighters in our report.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18]20,21 Concurrently, researchers 1,15,22,23 have reported that collegiate athletes in wrestling competitions and practice sessions experienced fewer cervical injuries than overall extremity injuries. Whereas wrestling-style arts and judo share features with MMA, the former do not include deliberate striking during practice and competitions, as MMA-style competition does.…”
Section: Discussionmentioning
confidence: 99%
“…49 For brevity, Table 3 shows percent range values for the most common injury locations as reported in recent sportspecific reviews on the epidemiology of pediatric sport-related injuries. [44][45][46][49][50][51][52][53][54][55][56] Most injuries are to the lower extremity. With few exceptions, the ankle and knee are the most common injury sites to the lower extremity, except for taekwondo in which injuries occur primarily to the foot and toes.…”
Section: Anatomical Locationmentioning
confidence: 99%
“…The more common types of injuries reported across sports are sprains and/or strains and contusions followed in different rank order -depending on sport, participation level, and gender -by lacerations, fractures, and inflammation. [44][45][46][49][50][51][52][53][54][55][56] Most studies report these injury types as a percentage of all injuries sustained, although several recent studies 26,32,37 report incidence rates for injury types, thus permitting comparison of rates across descriptive components. For example, football had the highest overall and game incidence rate for concussion in a recent study of high school athletes.…”
Section: Injury Typementioning
confidence: 99%